2019
DOI: 10.1186/s40497-019-0175-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of entrepreneurial motivation on entrepreneurial intentions and behaviour: theory of planned behaviour extension on engineering students in Pakistan

Abstract: The purpose of this paper is to extend theory of planned behaviour (TPB) model by focussing on intention-action gap, which is considered by academic researchers as under-researched area. It further examines the moderating role of entrepreneurial motivation between intention and behaviour (action) to enhance predictability of TPB on senior level engineering students in Pakistan. Survey conducted with 448 engineering students from four major engineering institutions for data collection. Structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 47 publications
10
89
0
2
Order By: Relevance
“…The results showed the consistency of the TPB and all antecedents of the TPB significantly contribute to explaining the entrepreneurial intentions among IT students relating to Pakistani context. Previous studies also show the consistency of the TPB in predicting entrepreneurial intentions among students from various disciplines regarding Pakistani context (Alam et al, 2019;Farrukh et al, 2018;Munir et al, 2019). The role of subjective norms in explaining entrepreneurial intentions differ across cultures and its effects on intentions according to the characteristics of the students.…”
Section: Discussionmentioning
confidence: 85%
“…The results showed the consistency of the TPB and all antecedents of the TPB significantly contribute to explaining the entrepreneurial intentions among IT students relating to Pakistani context. Previous studies also show the consistency of the TPB in predicting entrepreneurial intentions among students from various disciplines regarding Pakistani context (Alam et al, 2019;Farrukh et al, 2018;Munir et al, 2019). The role of subjective norms in explaining entrepreneurial intentions differ across cultures and its effects on intentions according to the characteristics of the students.…”
Section: Discussionmentioning
confidence: 85%
“…As constructs used in the model are latent constructs with multiple items of measurement, hence, multivariate technique SEM is most appropriate for this study. SEM is a widely used approach in management science and entrepreneurship based studies (Alam et al, 2019). In this study, PLS-SEM is used as it is considered suitable for complex models containing Role of knowledge sharing behaviour latent variables and the sole purpose is the investigation of relationships at the theoretical level (Hair et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The first gap is related to the relationship between motivation and intrapreneurship, as studies highlighting the role of motivation in intrapreneurship are rare. Although more established research is available on motivation and entrepreneurship (Alam et al, 2019). Various research studies have also reported this area in future research directions.…”
Section: Resultsmentioning
confidence: 97%
“…There is an inherent difference in the motivation level of individuals towards intrapreneurship and entrepreneurship. Motivation studies on the intrapreneurial engagement of engineers are limited though research on motivation of engineers towards entrepreneurial intentions is more established (Alam et al, 2019). Menzel et al (2007) mentioned that the sole beneficiary of entrepreneurial actions is individual.…”
Section: Intrapreneurship Actions By Engineersmentioning
confidence: 99%
See 1 more Smart Citation